2020
DOI: 10.12669/pjms.36.6.2312
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and pattern of Paediatric Heart Diseases: Five years experience at The Children’s Hospital, Multan

Abstract: Background & Objectives: Heart diseases in paediatric population are considered to be significant contributors to mortality and morbidity. Congenital heart disease (CHD) as well as acquired heart disease (AHD) are frequent causes of hospital admission among children. This study was aimed at finding out frequency and pattern of heart diseases in admitted patients at The Children’s Hospital, Multan. Methods: This study is a retrospective chart review of five years at Paediatric Cardiology Department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…16 Recent local data from Multan also correlates well with the present findings where the authors found VSD, ASD and TOF to be the most prevalent types of CHDs observed among 25.8%, 19.8% and 12.2% cases. 11 VSD is said to be the most frequent type of CHD worldwide and present study reiterates that VSD is also the most frequent type of CHD among Children in Pakistan. 17 In terms of risk factors evaluated for CHDs among children in the present study, young age, bad obstetrical history, history of febrile illness in 1 st trimester of pregnancy and lack of multivitamins and folic acid in the 1 st trimester of pregnancy were found to have significant association with the existence of CHD (p<0.05).…”
Section: Is Showing Comparison Of Characteristics Of Children Between Cases and Controlssupporting
confidence: 63%
See 2 more Smart Citations
“…16 Recent local data from Multan also correlates well with the present findings where the authors found VSD, ASD and TOF to be the most prevalent types of CHDs observed among 25.8%, 19.8% and 12.2% cases. 11 VSD is said to be the most frequent type of CHD worldwide and present study reiterates that VSD is also the most frequent type of CHD among Children in Pakistan. 17 In terms of risk factors evaluated for CHDs among children in the present study, young age, bad obstetrical history, history of febrile illness in 1 st trimester of pregnancy and lack of multivitamins and folic acid in the 1 st trimester of pregnancy were found to have significant association with the existence of CHD (p<0.05).…”
Section: Is Showing Comparison Of Characteristics Of Children Between Cases and Controlssupporting
confidence: 63%
“…Recent local data suggested 83.4% children with diagnosis of CHDs to be below 1 year of age. 11 Regional data also suggested 69.7% of the CHD cases to have age less than 1 year. 13 A local study revealed 71% children with CHDs to have age below 1 year.…”
Section: Is Showing Comparison Of Characteristics Of Children Between Cases and Controlsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our findings are consistent with other researchers where male predominance has been revealed among children with CHD. [14][15][16] Majority of the children (73.0%) were aged below 1 year. Data from other countries show that due to optimal predelivery and neonatal screening, majority of the CHD cases are diagnosed well within or before the neonatal age group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of healthcare facilities and diagnosis worsen the prognosis of congenital heart disease children [8]. Ventricular septal defect (VSD) and tetralogy of fallot (TOF) are considered as most common acyanotic and cyanotic heart disease respectively in Pakistan [9]. An Indian-based study reported the incidence of VSD, atrial septal defect (ASD), patent ductus arteriosus (PDA) were 30.4%, 17.6%, and 9.6% respectively [10].…”
Section: Introductionmentioning
confidence: 99%